Factors associated with wheezing in Indigenous children and adolescents: A systematic review of the global literature - Marcia Corrêa de Castro; Daniella Campelo Batalha Cox Moore; Karla Gonçalves Camacho; Saint Clair dos Santos Gomes; Margarida dos Santos Salú; Zina Maria Almeida de Azevedo; Sandra Lisboa; Andrey Moreira Cardoso (PLoS ONE, 2026)
Background Wheezing episodes are common in childhood and can occur due to different health conditions. Globally, Indigenous children are particularly affected, with a high burden of respiratory diseases related to socioeconomic inequalities, demographic characteristics, and exposure to environmental risks. Objective We summarize the knowledge available in the global literature on the determinants of wheezing in Indigenous children and adolescents and develop a theoretical model for analyzing them in Indigenous Brazilian children. Methods Systematic review conducted under the PRISMA 2020 criteria for studies, registered in PROSPERO (CRD42023395661). The Medline, Scopus, Web of Science, and LILACS databases were searched until September 2024. The inclusion criterion was analytical observational studies that showed risk factors for wheezing in children and adolescents (0–19 years). Studies that did not show specific results in the age group of interest, even if they included children and adolescents in their samples, book chapters, conference annals, or outcomes associated with chronic lung disease complications were excluded. Quality assessment was performed using the Newcastle-Ottawa Scale. Results Seventeen of the 263 analyzed studies were included in this systematic review, with a total of 139,783 participants. The most common design was cross-sectional (76.5%); most studies were conducted in North America (76.5%). Asthma was the most common type of wheezing episodes (88.2%). Male patients showed a more significant association with wheezing outcomes. Wheezing, when combined with asthma, was directly associated with age and inversely associated with age when accompanied by cold. Conclusion We identified three main factors for wheezing in Indigenous children and adolescents: Environmental (tobacco smoke, indoor pollution, and housing), socioeconomic (income, healthcare, and residence), and biological/clinical (sex, birth weight, infections, and allergies). We propose a model to analyze these factors in Indigenous Brazilian children. Differences in definitions, reliance on numerous cross-sectional studies, and focus on North America limit the generalizability of the results. Standardized methods and studies in new regions, particularly Brazil, are necessary for testing and refine this model.